Microplastic Contamination in Fish and Shellfish: A Review - Magvirah Tuljannah; Ramadhan Tosepu; Asramid Yasin; Jafriati; Ranno Marlany Rachman; Surya Cipta Ramadhan Kete (Journal of Epidemiology and Health Science, 2025)
Background: The continuous increase in global plastic production without adequate management has led to the entry of microplastics into aquatic ecosystems. The accumulation of these particles in marine biota, especially fish and shellfish, which are the main food sources for the Indonesian people, raises concerns about potential risks to human health. Objective: his article aims to review microplastic contamination in fish and shellfish in Indonesia and examine its implications for human health. Methods: This study used a literature review method by selecting 10 articles published between 2020 and 2025 from the PubMed, ScienceDirect, SpringerLink, Scopus, Google Scholar, and Garuda databases Results: Studies show that microplastics are consistently found in various fish species (e.g., Sardinella fimbriata, mackerel, red snapper) and blood clams (Anadara granosa) in Kendari, South Sulawesi, Java, Banten, and Southeast Asian waters. The dominant type is fiber, followed by fragments and film, with the main polymers being polyethylene (PE), polypropylene (PP), and polyamide (PA). Clams, as filter feeders, tend to accumulate higher levels of particles than fish, while spatial variations indicate the influence of local anthropogenic activities. From a health perspective, exposure to microplastics has the potential to cause tissue irritation, inflammation, and long-term toxicity due to their ability to adsorb hazardous chemicals. Conclusion: The study confirms that microplastic contamination in fish and shellfish is a serious issue in Indonesia with implications for public health. Mitigation efforts are needed through land-based plastic waste control, standardization of marine biota surveillance, and public education to reduce exposure risks.